A Palaearctic migratory raptor species tracks shifting prey availability within its wintering range in the Sahel. (8th November 2012) - Trierweiler, Christiane; Mullié, Wim C.; Drent, Rudi H.; Exo, Klaus‐Michael; Komdeur, Jan; Bairlein, Franz; Harouna, Abdoulaye; de, Marinus; Koks, Ben J.; Sandercock, Brett
Summary Mid‐winter movements of up to several hundreds of kilometres are typical for many migratory bird species wintering in Africa. Unpredictable temporary food concentrations are thought to result in random movements of such birds, whereas resightings and recoveries of marked birds suggest some degree of site fidelity. Only detailed (e.g. satellite) tracking of individual migrants can reveal the relative importance and the causes of site choice flexibility and fidelity. The present study investigates how mid‐winter movements of a Palaearctic‐African migratory raptor, Montagu's harrier Circus pygargus, in the Sahel of West Africa are related to the availability of food resources. Thirty harriers breeding or hatched in northern Europe were satellite tracked (2005–2009). On average, four home ranges, each separated by c. 200 km, were visited during one overwinter stay in the Sahel. Wintering home ranges were similar in size to breeding season home ranges (average over wintering and breeding home range size c. 200 km2), and harriers showed high site fidelity between years. Most preferred habitat types in the Sahel were mosaics of grass‐ and cropland, indicating similar habitat preferences in both the breeding‐ and wintering seasons. The main prey of Montagu's harriers in the Sahel were grasshoppers Acrididae. Highest grasshopper numbers in the field occurred at relatively low vegetation greenness [normalized difference vegetation index (NDVI) values 0·17–0·27]. We used NDVI as a proxy of food availability for harriers. During their overwinter stay, Montagu's harriers moved in a South–South‐western direction between consecutive home ranges. The birds selected areas within the range of NDVI values associated with high grasshopper numbers, thus tracking a 'green belt' of predictable changes in highest grasshopper availability. Contrary to earlier hypotheses of random movements in the Sahelian‐wintering quarters, the present study shows that Montagu's harriers visited distinct home ranges, they were site‐faithful and tracked seasonal changes in food availability related to previous rainfall patterns, caused by the shifting Intertropical Convergence Zone. Itinerancy may be the rule rather than an exception among insectivorous birds wintering in African savannahs.